Analysis of Factors Affecting Mother's Behavior in Giving Exclusive Breastfeeding to Infants aged 0-6 Months, in Bobonaro District, Timor Leste - Honorio Pereira Vicente; Sabina Gero; Marthen R. Pellokila (Rifa'Institute, 2022)
One of the efforts to reduce the risk of infant mortality is through the provision of Exclusive Breastfeeding (ASI) from the beginning of birth and then continued with breastfeeding. The practice of giving solid complementary foods can inhibit the growth of newborns. The purpose of this research is to describe and analyze the factors that influence the mother's behavior in exclusive breastfeeding for infants aged 0-6 months in Bobonaro District, Timor Leste. The research design is descriptive analytic with a cross-sectional approach. The research sample was 84 mothers giving birth using simple probabilities. Data were analyzed using logistic regression test (binary logistic). The results showed that 67.9% of mothers who gave exclusive breastfeeding to infants aged 0-6 months in Bobonaro District. Mother's education factor, mother's knowledge, mother's attitude, support for health services, support from mother's family and exposure to information have an influence on mother's behavior in breastfeeding, each of which has a p value > 0.05. Mother's socio-cultural factors and distance of health services did not have an influence on the behavior of mothers in giving exclusive breastfeeding, each obtained a p value <0.05. Health workers as supporters of the success of exclusive breastfeeding, should increase health education programs about exclusive breastfeeding to mothers and their families in detail and continuously, so that mothers giving birth and their families can know and understand the importance of breastfeeding, and can change the behavior of mothers giving birth and their families.